Basında fotoğrafın kullanılması fotoğrafın altyazı ile birlikte olayı ve durumu biçimlendirmesi - Türker, Nurdan (My University, 2006)
Fotoğraflar, zamanın akışından çekilip alınmış anlardır. Fotoğrafçı, deklanşöre basarak o anı dondurur, korumaya alır ve yok olmasını engeller. Çekilen bu fotoğraf, çekilebilecek diğer binlerce fotoğraf karesinden sadece birisidir. Önceki ve sonraki karelerin arasında olandır. Fotoğraf belli bir geçmişten gelen şimdinin, geleceğin ruhuyla karıştığı geçici anı dondurur. Fotoğrafın anlamı durağan değildir ve her zaman anlam kendisinden kaynaklanmaz. Fotoğrafların kullanım yer ve biçimleri, onların bize sunuldukları bağlam, nasıl algıladığımızı, nasıl etkilendiğimizi doğrudan tanımlar. Fotoğraf, anlam üretmede ve yaratmada çok etkili bir görsel malzemedir. Fotoğraflı haber metnin anlamlandırılmasını hızlandırır ve kolaylaştırır. Altyazılar, fotoğrafın içeriğini tanımlayarak, bilgiyi detaylandırır ve yeni kavrayışların yolunu açarlar. Bu araştırmanın konusunu, fotoğraf – altyazı ilişkisi, yazının fotoğrafı nasıl etkilediği, fotoğrafın bağlamına göre anlamının nasıl değiştiği oluşturmaktadır. Bu tezin temel amacı, basında fotoğraflar üzerinden, fotoğraf – altyazı etkileşimiyle oluşan yeni bağlamın anlam oluşturmadaki gücüne dikkatleri çekmektir. Birinci bölümde, imge - sözcük, ikinci bölümde fotoğraf – sözcük ilişkileri örneklerle incelenmiştir. Üçüncü bölümde; basında fotoğrafın kullanımı, haber fotoğraflarının habere katkıları, gazetelerde organizasyon ve gazetelerin birinci sayfaları ve önemi konuları ele alınmıştır. Dördüncü bölümde, fotoğraf – altyazı ilişkisi irdelenmiş, altyazı sınıflanlandırılması hakkında bilgi verilmiştir. Tezin beşinci bölümünde ise, basında fotoğraf - altyazı ilişkisine yönelik bir uygulama yapılarak gazetelerde fotoğrafın altyazıyla olan ilişkisi ve duruma etkisi tanımlanmaya çalışılmıştır. Bu amaçla, konu olarak İsrail’in Lübnan’a saldırısı seçilmiş, saldırı başlangıç tarihi ile ateşkes tarihi arası periyod olarak belirlenmiştir. Gazetelerin birinci sayfalarının, gazeteler için önemi göz önüne alınarak, saha çalışması gazete birinci sayfa fotoğrafları olarak sınırlandırılmıştır. Altyazısı olan fotoğraflar sınıflandırılarak, fotoğraf – altyazı uygulaması ve etkileşimleri tanımlanmaya çalışılmıştır.

Photographs are moments stolen from the flow of time. A Photographer freezes that moment by pressing the shutter release and with that release the moment stays visually preserved, saved from becoming lost forever. In actuality that moment is one moment chosen from among thousands. A photograph freezes the ephemeral where ‘now’ coming from the tracks of the past meets with the soul of the future. A photograph may appear to be a still image, but its meaning is not fixed and resonates from sources beyond the actual image. How we perceive photographs and how they affect us can be traced directly to their place of usage and form i.e from the context of how they are presented to us. A photograph is very effective visual material on the generation and creation of sense and meaning. News accompanied by photographs accelerate and ease interpretation. Captions detail the news and open new ways of understanding by describing the content of the photograph. The subject of this research is to outline the relation between caption- photograph, specifically how the written word affects the photograph and how the interpretation and perception of photographic images changes with respect to its context. The main aim of this thesis is to draw attention to the power of photographs in the press to create meaning from the context that arises when photographs are paired with captions. In the first chapter the relation between image - word and in the second the relation between photograph – word are examined with examples. The contents of the third chapter are the following: the usage of photographs in the press, the contribution of news photographs to the news itself, the organizational layout of newspapers and the importance of front pages. The relation between photographs and caption is discussed in the fourth chapter along with information about caption classification. In the fifth chapter the relation between caption and photograph is examined through an applied study/ research that was performed with newspapers as the source. The aim of this application is to describe caption - photograph relations and define their effect on the creation of meaning. The study focused on Israel’s military attack on Lebonan during the summer of 2006. The time interval chosen was between the starting date of the attacks through the ceasefire. The study/ research was limited to an examination of front page photographs of newspapers in view of their importance journalistically. Classifying photographs with captions, the study/ research endeavors to define the applications of and interplay between photographs and captions.
Keywords: Fotoğrafçılık